In vitro evaluation of magnetite nanoparticles in human mesenchymal stem cells: comparison of different cytotoxicity assays. (2nd January 2020) - De Simone, Uliana; Spinillo, Arsenio; Caloni, Francesca; Avanzini, Maria Antonietta; Coccini, Teresa
Abstract: This work was aimed at defining the suitable test for evaluating Fe3 O4 NPs cytotoxicity after short-term exposure in human mesenchymal stem cells (hMSCs) using different viability tests, namely NRU, MTT and TB assays, paralleled by cell morphology analyses for cross checking. MTT and NRU data (culture medium with/without hMSCs plus Fe3 O4 NPs) indicated artificial/false increments in cell viability after Fe3 O4 NPs. These observations did not fit with the morphological analyses showing reduced cell density, loss of monolayer features, and morphological alterations at Fe3 O4 NPs ≥50 μg/ml. Fe3 O4 NPs alone induced a substantial increased absorbance at the wavelength required for MTT and NRU. A significant death (25%) of hMSC at Fe3 O4 NPs ≥10 μg/ml, with a maximum effect (45%) at 300 μg/ml after 24 h, exacerbated after 48 h, was observed when applying TB test. These results paralleled the effects on cell morphology. The optical properties and stability of Fe3 O4 NP suspension (tendency to agglomerate in a specific culture medium) represent factors that limit in vitro result interpretation. These findings suggest the non applicability of the spectrophotometric assays for hMSC culture conditions, while TB is an accurate method for determining cell viability after Fe3 O4 NP exposure in this model. In relation to NPs safety assessment: cell-based assays must be considered on case-by-case basis; selection of relevant cell models is also important for predictive toxicological studies; application of a testing strategy is fundamental for understanding the toxicity pathways driving cellular responses.